Sequence‐Dependent dsDNA‐Templated Formation of Fluorescent Copper Nanoparticles. Issue 6 (15th December 2014) - Song, Quanwei; Shi, Yu; He, Dacheng; Xu, Shenghao; Ouyang, Jin
Abstract There are only a few systematic rules about how to selectively control the formation of DNA‐templated metal nanoparticles (NPs) by varying sequence combinations of double‐stranded DNA (dsDNA), although many attempts have been made. Herein, we develop a facile method for sequence‐dependent formation of fluorescent CuNPs by using dsDNA as templates. Compared with random sequences, AT sequences are better templates for highly fluorescent CuNPs. Other specific sequences, for example, GC sequences, do not induce the formation of CuNPs. These results shed light on directed DNA metallization in a sequence‐specific manner. Significantly, both the fluorescence intensity and the fluorescence lifetime of CuNPs can be tuned by the length or the sequence of dsDNA. In order to demonstrate the promising practicality of our findings, a sensitive and label‐free fluorescence nuclease assay is proposed.